2008
DOI: 10.1104/pp.108.120477
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of Arabidopsis Postprenylation CaaX Processing Enzymes and Their Function in Subcellular Protein Targeting    

Abstract: Prenylation is a posttranslational protein modification essential for developmental processes and response to abscisic acid. Following prenylation, the three C-terminal residues are proteoliticaly removed and in turn the free carboxyl group of the isoprenyl cysteine is methylated. The proteolysis and methylation, collectively referred to as CaaX processing, are catalyzed by Ste24 endoprotease or Rce1 endoprotease and by an isoprenyl cysteine methyltransferase (ICMT). Arabidopsis (Arabidopsis thaliana) contains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
48
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 63 publications
0
48
0
Order By: Relevance
“…However, a T-DNA insertion three nucleotides upstream of the TGA codon of STE14A was recently reported (Bracha-Drori et al, 2008). This mutant exhibited no detectable STE14A mRNA and no observable phenotype, suggesting that its function is either dispensable or redundant with that of STE14B.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a T-DNA insertion three nucleotides upstream of the TGA codon of STE14A was recently reported (Bracha-Drori et al, 2008). This mutant exhibited no detectable STE14A mRNA and no observable phenotype, suggesting that its function is either dispensable or redundant with that of STE14B.…”
Section: Discussionmentioning
confidence: 99%
“…This mutant exhibited no detectable STE14A mRNA and no observable phenotype, suggesting that its function is either dispensable or redundant with that of STE14B. Transgenic plants containing an STE14B RNA interference (RNAi) construct did not exhibit a significant decrease in STE14B mRNA abundance, but a subtle phenotype was observed (Bracha-Drori et al, 2008), suggesting that either STE14B silencing occurred at the level of translation or another gene was affected by the RNAi construct (no data were presented to demonstrate reduced ICMT protein or activity). These plants exhibited altered phylotaxis, multiple axillary buds, and fasciated stems, but they did not exhibit an ABA-hypersensitive phenotype (Bracha-Drori et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on their amino acid sequences, RAC/ROPs have been divided into two subgroups, designated type I and type II (Winge et al, 2000). Type I RAC/ROPs terminate with a canonical CaaL motif and are attached to the membrane following prenylation in the cytoplasm by the protein geranylgeranyltransferase-I (Sorek et al, , 2011 and CaaX processing in the endoplasmic reticulum (ER) (Bracha-Drori et al, 2008). Type II RAC/ROPs terminate with a GC-CG box sequence motif and are attached to the plasma membrane by S-acylation (palmitoylation) (Lavy et al, 2002;Lavy and Yalovsky, 2006).…”
mentioning
confidence: 99%
“…SCO4 is a protein whose homologs are present in higher plants, according to the data sets produced by GreenCut (Grossman et al, 2010), and, by our analysis, are distantly related to but do not have the function of the canonical CaaX-type endopeptidases, RCE1 and STE24 (Bracha et al, 2002;Bracha-Drori et al, 2008) that are found throughout eukaryotes, both plant and animal (Fig. 9).…”
Section: Sco4 Is a Novel Plant-specific Chloroplast Endopeptidasementioning
confidence: 99%